Pengembangan Aplikasi Service Open Journal System (OJS) (Studi Kasus : FILKOM UB) - Muhammad Ridwan; Denny Sagita Rusdianto; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Journal of Information Technology and Computer Science (J-PTIIK) Development of Brawijaya University is a repository of scientific journals that contains scientific writings from students of the Faculty of Computer Science Universitas Brawijaya. J-PTIIK is a repository of scientific journals supported by an open source journal management platform, the Open Journal System (OJS). In the application of the journal to be included in the repository, an editor must check it by checking all the files entered in the OJS and checking whether the scientific journals uploaded in the OJS are the same as the research done in FILKOM's thesis system. Journal editors must open two different applications to check the correctness of data from a student's scientific journal. To get student data from the FILKOM thesis system the editor must search the name of the student to get the data. This is not efficient because journal editors examine journals by opening two different systems and will take longer if there is a high number of students making publications. By integrating the two systems the editor is expected to simply access one application. This service was developed with one of the micro frameworks, namely the slim framework. The results of unit testing, integration testing and validation testing resulted in a 100% valid value and efficiency testing increased 10.79%